2020
DOI: 10.5114/nan.2020.101293
|View full text |Cite
|
Sign up to set email alerts
|

A study of disability profile and burden in caregivers of stable schizophrenia patients

Abstract: Introduction: Schizophrenia is one of the most devastating disorders, leading to long-term and progressive disability in numerous individuals. Disability reflects an interaction between features of a person's body and of the society. In all treatments, family psycho-education is also very important as disability of schizophrenia leads to burden upon family members. Caregiver burden can be either objective or subjective. Objective burdens are behavioural phenomena: disruption of the social activities and financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…In contrast, (63) found a significant relationship between gender and burden in their study conducted in India. When compared to male caregivers, both females and wives perceived more burden as caregivers.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In contrast, (63) found a significant relationship between gender and burden in their study conducted in India. When compared to male caregivers, both females and wives perceived more burden as caregivers.…”
Section: Discussionmentioning
confidence: 77%
“…on the contrast of that (64) in their study conducted in Egypt reported that there was no significant relationship between the level of education and caregiver burden. In addition, a study conducted in India (63) revealed that there is no relationship between education and burden.…”
Section: Discussionmentioning
confidence: 99%
“…The sociodemographic profile of dyads in polypathology is similar to other profiles reported in Colombia in terms of chronicity, where intervention has not necessarily been carried out. This indicates that the phenomenon of polypathology may have been around for many years in Colombia, and only with this study that focuses on polypathology is it beginning to be recognized as important to address from an innovative and relevant model such as case management 14,15 .…”
Section: Discussionmentioning
confidence: 97%
“…This study was designed to assess the associations between caregivers' quality of life. Moreover, the traditional approach to caregiver's related variables divided into subjective and objective variables (Modi et al 2020) was analysed. The objective factors were functional abilities and daily independence of people with dementia, time devoted to care, and caregiver's sleep patterns.…”
Section: Discussionmentioning
confidence: 99%